The Influence of Pressure, Opportunity, Rationalization, Capability, Arrogance, and Collusion on Village Fund Fraud with Morality as a Moderating Variable - Suryandari Erni; Moaffafah (SHS Web of Conferences)
This research aims to determine the influence of pressure, opportunity, rationalization, capability, arrogance, and collusion on village fund fraud with morality as a moderating variable in the village government of Sampang Regency. The subjects of this research were village government officials, including the villagehead, village secretary, and head of financial affairs, who had served or were currently serving for at least two years, employing a purposive sampling technique. In this research, the primary survey research method was used by distributing 216 questionnaires to 72 villages in Sampang Regency. A total of 180 questionnaires were returned and can be processed utilizing SmartPLS software version 4.0.9.8. The results of this research unveiled that capability and arrogance positively influenced village fund fraud, and morality could weaken the positive influence of opportunity and arrogance on village fund fraud.